Bone Replacement: The Secretome of Hypoxia Conditioned hMSC Loaded in a Central Depot Induces Chemotaxis and Angiogenesis in a Biomimetic Mineralized Collagen Bone Replacement Material (Adv. Healthcare Mater. 2/2020). Issue 2 (22nd January 2020) - Quade, Mandy; Münch, Pina; Lode, Anja; Duin, Sarah; Vater, Corina; Gabrielyan, Anastasia; Rösen‐Wolff, Angela; Gelinsky, Michael
Abstract : In article number 1901426 by Anja Lode and co‐workers, sustained release of hypoxia‐conditioned MSC secretome from a central depot induces directed hBMSC migration and angiogenesis in biomimetic mineralized collagen scaffolds. This in situ tissue engineering concept is suggested to be a cell‐free and ready‐to‐use therapeutic solution for accelerated bone defect healing.